2002
DOI: 10.4319/lo.2002.47.3.0856
|View full text |Cite
|
Sign up to set email alerts
|

Saharan input of phosphate to the oligotrophic water of the open western Mediterranean Sea

Abstract: A Saharan soil, considered as a proxy for Saharan aerosols, was used to perform a series of dissolution experiments: various amounts of Saharan soil were exposed to ultrapure water and seawater for varying lengths of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
187
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(209 citation statements)
references
References 55 publications
(66 reference statements)
17
187
1
4
Order By: Relevance
“…Thus, the response of the Z treatment (N limited) after 48 h as somewhat lower than ZN (P limited) for both variables and was significantly lower than the response of the ZNA treatment where the added limiting nutrient P concentration was 40 times higher than Z and ZN (Figures 2, 3). This confirms that the dust provided a bioavailable (leachable) source of N and P as found in other studies (Herut et al, , 2002Migon et al, 2001;Ridame and Guieu, 2002) and relieved the phytoplankton community of N and P co-limitation (Kress et al, 2005;Krom et al, 2005;Pitta et al, 2005;Tanaka et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Thus, the response of the Z treatment (N limited) after 48 h as somewhat lower than ZN (P limited) for both variables and was significantly lower than the response of the ZNA treatment where the added limiting nutrient P concentration was 40 times higher than Z and ZN (Figures 2, 3). This confirms that the dust provided a bioavailable (leachable) source of N and P as found in other studies (Herut et al, , 2002Migon et al, 2001;Ridame and Guieu, 2002) and relieved the phytoplankton community of N and P co-limitation (Kress et al, 2005;Krom et al, 2005;Pitta et al, 2005;Tanaka et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Chen et al [2006] extracted aerosol samples in pure water for 30 min with sonication and obtained slightly higher SRP yields than with samples extracted in low-nutrient seawater (LNSW). Ridame and Guieu [2002] also observed greater SPR yields in pure water than in LNSW for gently stirred solutions containing Saharan soil particles. However, Nehring [1976] found that although the extraction rate of P from Saharan dust was slower in seawater than in pure water, the amount of extractable P was similar when longer extraction times were used.…”
Section: Sample and Data Analysismentioning
confidence: 90%
“…It is unclear whether Chen et al [2006] would have obtained different results if they had employed a longer extraction time. Also, neither Chen et al [2006] nor Ridame and Guieu [2002] used buffered pure water for their extractions.…”
Section: Sample and Data Analysismentioning
confidence: 99%
“…Two exposure durations were chosen to simulate natural conditions: 24 hours and 7 days. These exposure durations were assumed to be representative of the contact time between the atmospheric particles and seawater [Ridame and Guieu, 2002]. During incubations, the flasks were stirred every 12 hours.…”
Section: Methodsmentioning
confidence: 99%